O desenvolvimento da escrita de estudantes com deficiência intelectual: uma análise sobre o uso de recursos de comunicação aumentativa e/ou alternativa no atendimento educacional especializado - Castro, Janaina Luiza Moreira de (2019)
The present research is based on the estimated theoreticians partner-descriptions and objectified to analyze the contributions of the Augmentative Communication and/or Alternativa (CAA) for the learning of the written language of pupils with Intellectual Disability (ID) in the context of Specialized Educational Assistance (AEE). It also aimed to identify the initial characteristics of the written language of students with ID in the literacy process and to investigate the repercussions of the mediation of an teacher through the use of the AAC to learn the written language of students with ID. Participants in this research were an ESA teacher and three students diagnosed with intellectual disability, whose writing was in the process of development between pre-syllabic and syllable-alphabetic levels. The students in the study were enrolled in a public school of the municipal education network of Fortaleza, CE, in Elementary School, in rooms of the 2nd, 3rd and 6th years. The qualitative study of the intervention type comprised four stages: 1) application of evaluative activities of the conceptual level of written language of students with ID; 2) interview with the ESA teacher and application of self-assessment questionnaire / questionnaire; 3) observations of the pedagogical practice of the ESA teacher in SRM; 4) planning in collaboration with the ESA teacher to carry out intervention sessions using the CAA resources in the SRM. The results indicated that the mediation strategies of the ESA teacher with the use of CAA resources provoked the emergence and appropriation of writing strategies of the research participants. It was also verified that the students with DI evolved conceptually within the very psychogenetic level of writing in which they found themselves. It is concluded that the diversified use of mediation strategies by the ESA teacher, through a constant work of reflection on the alphabetic writing system, raised questions in the students and assisted them in overcoming their writing hypotheses.